SMART WASTE MANAGEMENT SYSTEM USING IMAGE PROCESSING. - SRIDEVI, A.; GOWTHAM, A.; RAGUNATH, R.; KRISHNA, K. VAMSHI (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Waste management in big cities like Mumbai, Kolkata, Delhi, Chennai, Hyderabad, and other metropolitan cities is a very big challenge. It degrades the environmental conditions in those cities and its quality is spoiled by the residents. Over the last fewyears, there has been a several improvements towards this area by introducing home waste collection. The main idea is about achieving support from residents who are living in that particular area surrounding the waste. A digital equipment along with the components has been used to develop the waste collection from residents. An IoT has been used as a key solution to achieve this process. The regular waste management system can be replaced with number of sensors in the system along with AI (Artificial Intelligence) to achieve good waste classification. This project is to achieve smart waste classification system using IoT and deep learning model based on AI. Hardware sensors are used to resolve the data status of the bin and Image Processing program which is coded in python language is used to carry out the object detection and classification. Object detection and segregation of waste is performed by AI based framework with pre-trained object detection model. This model is trained with images of the waste of various types and it generates frozen interference graph. Object detection is done by using camera which is connected with the PC. PC serves as key processing unit. Ultrasonic sensor is placed on each waste bin to check the level of the waste filling available in the bin.